(3GdSHjcI GdPgHjI aj CYGQjV GdYQHjIs - (3GdgfOj, GdfLaj, eMeO Hf gGTe Hf TLGYI Ydj, J(B1323(3g`s ((3YR GdOjf Hf eMeO LhGO GdLRGFQjs)
(3ChdgG (B:s
(3GdMeO ddg HGQF GdHQGQj hGdHMhQ(B...(3gPg QSGdI aj GdYQhV fGaYI eTJedI Ydi eWGdHg eGfYI LGeYI (B...s
(3BNQgG (B:s
(3hjONd GdYQhV GdChdi GdMPa hdG jchf dGReG Hd jONd aj HjJ hdG jONd aj BNQ aj GdbUjLI GdhGMOI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B129s
(3GdPQjYI(B:(3L(B12(3,U(B99(3,Qbe(B920s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdYQhV hGdbhGajs